Islamic Boarding House as a Learning-Living Lab: A Model for Building a Culture of Worship, Knowledge, and Togetherness Among Students - Rokhmani; Muhammad Nizarudin; Siti Surotul Khasanah; Lena Dwi Prihatin; Afdhal Khubaba; M Rikza Chamami (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2026)
Student housing is no longer merely a residence, but a developmental space that shapes habits, character, and a learning environment affecting students’ intellectual, spiritual, and social maturity. In this context, Islamic boarding houses (kost islami) hold potential to develop as learning-living laboratories that integrate a culture of knowledge, worship practices, and communal engagement within one educational ecosystem. This study aims to analyze how Islamic student housing functions as a holistic learning space that supports the formation of adab, academic productivity, and meaningful social relationships. This research employed a qualitative case study approach through observations, in-depth interviews, and documentation of daily activities. The findings indicate that intellectual interactions, worship routines, and social bonding emerge naturally among residents, although they are not yet supported by structured management or formal community programs. The integration of these three pillars contributes to character building and fosters balance between academic demands and spiritual well-being. The study concludes that Islamic student housing has strong potential to serve as a learningliving laboratory, yet requires strengthened management systems, structured mentorship, and programmed activites to ensure continuity and maximize its role within the framework of modern Islamic education.